Kinetics of phytate hydrolysis during storage of red kidney beans and the implication in hard-to-cook development. (September 2022) - Wainaina, Irene; Wafula, Elizabeth; Van Loey, Ann; Sila, Daniel; Hendrickx, Marc; Kyomugasho, Clare
Graphical abstract: Highlights: Red kidney beans stored at varying moisture content and temperature were analyzed. Phytate (InsP6 ) hydrolysis resulted in formation of inositol pentaphosphate (InsP5 ). InsP6 hydrolysis was influenced by temperature with little effect of moisture content. Storage above overall glass transition temperature (Tg ) (T − Tg ) did not fully explain InsP6 hydrolysis. InsP6 hydrolysis during storage positively correlated with HTC development during storage. Abstract: In this study, the kinetics of phytate (inositol hexaphosphate, InsP6 ) hydrolysis by endogenous phytase in red kidney beans stored at varying conditions of temperature (25–42 °C) and moisture content (6.9–14.5%) was determined and the potential role in hard-to-cook (HTC) development was evaluated. In addition, the concept of glass transition temperature (Tg ) was assessed and correlated against the rate of phytate hydrolysis. Under the conditions studied, phytate hydrolysis during storage was mainly influenced by storage temperature and time with limited influence of storage moisture content whereby the highest and lowest storage temperatures (42 °C and 25 °C) resulted in the highest and lowest hydrolysis rates (0.058 ± 0.003 and 0.003 ± 0.001 week −1 ). Hydrolysis of phytate resulted in formation of lower inositol phosphates, inositol pentaphosphate (InsP5 ) representing an intermediate whose concentration increased with storage time and temperature. The relationship between the rate of InsP6 hydrolysis and storage above the overall Tg (T − Tg ) was moisture content dependent implying that this difference did not fully explain InsP6 hydrolysis. Nevertheless, for each moisture content, the rates of InsP6 hydrolysis during storage were strongly correlated (r > 0.98, p < 0.05) with rates of HTC development signifying that InsP6 hydrolysis facilitates HTC development in beans.